Rural Transformation, Water Scarcity and Policy Responses in China - Jinxia Wang; Zhiyi Guo; Dong Wang; Kaixing Huang; Zhuanlin Wang; Ruoying Mei; Rujuan Li; Jikun Huang; Chenhui Zhang; Chunlai Chen (Asia & the Pacific Policy Studies)
ABSTRACT This study examines the complex interplay between rural transformation and water scarcity in China, focussing on how shifts towards high‐value agriculture and non‐farm employment affect water resources. Utilising data spanning 2 decades, it evaluates the impact of economic activities on water scarcity through the lens of the Environmental Kuznets Curve. The analysis reveals regional variations in water usage and scarcity, highlighting the need for tailored water management strategies that incorporate both supply and demand aspects. By aligning rural economic development with sustainable water use, the paper offers insights into policy adjustments crucial for balancing growth with environmental stewardship, particularly in light of Chinaʼs green economy transition and its implications for similar developing regions.